1995
DOI: 10.1093/oxfordjournals.humrep.a135827
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between an asymptomatic male genital tract exposure to Chlamydia trachomatis and an autoimmune response to spermatozoa

Abstract: The relationship between a localized genital tract humoral immune response to Chlamydia trachomatis and the presence of antisperm antibodies on the surface of motile spermatozoa in the ejaculate was examined in 227 asymptomatic male partners of infertile couples with no history of exposure to C.trachomatis. Semen and serum samples were assayed for immunoglobulin (Ig) A and IgG antibodies to C.trachomatis by enzyme-linked immunosorbent assay employing a recombinant Chlamydia-specific lipopolysaccharide fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 0 publications
3
54
0
2
Order By: Relevance
“…The effect of latent C. trachomatis on semen quality and urogenital organs is debatable [5,9,10]. There have been few studies on the long-term consequences of persistent asymptomatic C. trachomatis infections of the male genital tract [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of latent C. trachomatis on semen quality and urogenital organs is debatable [5,9,10]. There have been few studies on the long-term consequences of persistent asymptomatic C. trachomatis infections of the male genital tract [9].…”
Section: Discussionmentioning
confidence: 99%
“…The role of semen microbiology in treating cases of male infertility remains controversial [5,9,10]. Chlamydia trachomatis infections of the male and female genital tracts are often asymptomatic, and may thus persist undetected for long periods of time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antichlamydial IgA detection in seminal plasma is a highly specific test for C. trachomatis diagnosis that has good agreement with other speciesspecific methods, such as ELISA, and more sensitivity than microimmunofluorescence [4,25]. There is an association between the presence of IgA antibodies to C. trachomatis in semen and alterations in some seminal parameters such as motility or leucocytospermia [25,34]. Nevertheless, other authors have not found such a relationship [16,27].…”
Section: S Penna Videaú Et Almentioning
confidence: 95%
“…Anti-sperm antibodies may also be formed as a result of cross-reactivity between sperm antigens and bacterial antigens (Witkin et al, 1995). A complete understanding of the mechanism behind immunologic infertility, as well as improved diagnosis and treatment, depends on knowledge of the identities of specific sperm antigens capable of eliciting the production of functionally relevant sperm antibodies.…”
Section: Introductionmentioning
confidence: 99%